2010
DOI: 10.1007/s11095-010-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity and Its Relationship with Passive Drug Permeation

Abstract: In this review, we first summarize the structure and properties of biological membranes and the routes of passive drug transfer through physiological barriers. Lipophilicity is then introduced in terms of the intermolecular interactions it encodes. Finally, lipophilicity indices from isotropic solvent systems and from anisotropic membrane-like systems are discussed for their capacity to predict passive drug permeation across biological membranes such as the intestinal epithelium, the blood-brain barrier (BBB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
241
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(252 citation statements)
references
References 112 publications
5
241
0
6
Order By: Relevance
“…14 In support of this notion it was also found that logP oct-alk correlates with brain penetration and oral absorption. 15,16 Recent systematic work incorporating IMHB considerations in drug design has been published by Kuhn and coworkers. 17 On the basis of pioneering work by Etter 18 and Bilton 19 and exhaustive searches of crystal structure databases, they derived propensities for IMHB formation of five-to eight-membered ring systems of relevance in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In support of this notion it was also found that logP oct-alk correlates with brain penetration and oral absorption. 15,16 Recent systematic work incorporating IMHB considerations in drug design has been published by Kuhn and coworkers. 17 On the basis of pioneering work by Etter 18 and Bilton 19 and exhaustive searches of crystal structure databases, they derived propensities for IMHB formation of five-to eight-membered ring systems of relevance in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that logP oct-alk is informative of IMHB and the reports that logP oct-alk correlates with brain penetration and oral absorbtion 15,16 lead us to explore logP oct-tol (logP oct-tol = logP octlogP tol . [25][26][27][28][29] The investigation of IMHB by logP was proposed some time ago 30 , however this approach was not widely implemented mainly because the practical tools, both experimental and theoretical, to obtain logP alk data for large series of compounds were limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the difference between two log P values (log P) obtained in different biphasic systems for example octanol/water and alkane/water (log P oct-alk = log P oct -log P alk ), is informative of the solutes HBD properties (Abraham et al, 2010b) and thus useful in the prediction of drugs human fate (Liu et al, 2011). The recent interest for the application of log P oct-alk in the drug discovery process stimulated the research for the design and implementation of tools for its prediction (Caron and Ermondi, 2005) (Toulmin et al, 2008) (Kenny et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…La hidrofobicidad molecular fue incluida en los modelos QSAR mediante el coeficiente de partición n-octanol/agua (LogP o/w ), que mide la permeabilidad de las membranas biológicas hacia una molécula en particular. 42,43 Los LogP o/w fueron calculados utilizando la versión online del programa ALOGPS 2.1 siguiendo el esquema propuesto por Tetko y colaboradores. 44,45 Metodología QSAR La construcción de los modelos QSAR se llevó a cabo mediante el análisis de regresión lineal múltiple (MLR, por sus siglas en inglés) implementado en el software BuildQSAR.…”
Section: Metodología Computacionalunclassified